RABIES, PENYEBAB DAN MANAJEMEN PRA-PAJANAN SERTA PASCA-PAJANAN - Hemavalli Ragunathan (DiscoverSys Inc., 2016)
Rabies is an acute viral disease that causes fatal encephalomyelitis in virtually all the warm-blooded animals including man. The virus is found in wild and some domestic animals, and is transmitted to other animals and to humans through their saliva (i.e. following bites, scratches, licks on broken skin and mucous membrane). Guidelines throughout worldwide quote that dogs are responsible for about 97% of human rabies, followed by cats (2%), jackals, mongoose and others (1%). The disease is mainly transmitted by the bite of a rabid dog.